2017
DOI: 10.7754/clin.lab.2017.170327
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs Expressions and Interaction with Biological Systems in Patients with Alzheimer`s Disease. Using miRNAs as a Diagnosis and Prognosis Biomarker

Abstract: For the evaluation and non-invasive monitoring of patients with Alzheimer`s disease the expression of miRNAs can be successfully used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…[43][44][45][46] The transporting protein, Exportin 5, will then act on the pre-miRNAs, which will transfer the epigenetic complex from the nucleus to the cell cytoplasm. [47][48][49] Once the signal that the complex has reached the cytoplasm is received, RNA polymerase III (Dicer) and trans-activator RNA binding protein (TRBP) attack it and lead to the formation of mature miRNAs. 5,50 This molecular species is then introduced in Furthermore, regarding the action mechanisms, researchers came to the conclusion that miRNAs are involved in inflammation, in the redox response, nutrient sensing, and silent mating-type information regulation 2 homolog (SIRT1)-regulated events.…”
Section: The Most Common Molecular Mechanisms Involved In Cvdsmentioning
confidence: 99%
“…[43][44][45][46] The transporting protein, Exportin 5, will then act on the pre-miRNAs, which will transfer the epigenetic complex from the nucleus to the cell cytoplasm. [47][48][49] Once the signal that the complex has reached the cytoplasm is received, RNA polymerase III (Dicer) and trans-activator RNA binding protein (TRBP) attack it and lead to the formation of mature miRNAs. 5,50 This molecular species is then introduced in Furthermore, regarding the action mechanisms, researchers came to the conclusion that miRNAs are involved in inflammation, in the redox response, nutrient sensing, and silent mating-type information regulation 2 homolog (SIRT1)-regulated events.…”
Section: The Most Common Molecular Mechanisms Involved In Cvdsmentioning
confidence: 99%
“…10,11 Furthermore, miRNAs exert these function in various human cancers and serve as a kind of biomarkers. 12 MiR-186-5p, an endogenous miRNA, has been reported to exert function as a tumor suppressor in osteosarcoma and inhibits cell proliferation as well as metastasis through regulation of zinc nger E-box binding (ZEB) in human colorectal cancer. 13 Besides, Lin et al reported that microRNA-186-5p (miR-186-5p) induced chronic myeloid leukemia (CML) cell apoptosis and reduced cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that miRNAs are involved in the regulation of human cancers and can be used as the diagnosis and therapeutic targets [22,23]. For instance, miR-96 is upregulated in breast cancer and promotes breast cancer metastasis by suppressing MTSS1 [24].…”
Section: Discussionmentioning
confidence: 99%